Job Satisfaction of Civil Engineers Working in Local Level Government in Bagmati Province, Nepal - Upadhaya, Arjun; Nepal, Sujan; Pokhrel, Sudip; Rawat, Bikram (Journal of Engineering Issues and Solutions, 2025)
This study explores the job satisfaction of Civil Engineers working in local governments across Bagmati Province, Nepal. These professionals play a vital role in infrastructure development, yet face challenges such as project delays, cost overruns, and demotivating staff adjustment policies. A total of 169 Civil Engineers were surveyed using structured questionnaires to assess their satisfaction levels across various job-related factors by single Global Rating Method and Summation of Job Factor Method. The findings reveal overall dissatisfaction, particularly with pay, which had the lowest mean score of 2.734. In contrast, supervision received the highest satisfaction score of 3.877. Statistical analysis indicates significant positive relationships between job satisfaction and key workplace factors. A multiple linear regression model shows that these factors collectively explain 71.2% of the variation in job satisfaction. While gender and work location had no significant influence, job designation and appointment type were found to impact satisfaction levels. The study highlights the need for improvements in working conditions, particularly in compensation, career progression, and administrative policies. Enhancing these areas can contribute to better motivation, retention, and performance of Civil Engineers, ultimately supporting more efficient infrastructure development at the local level.